Climate change, air pollution and global challenges : understanding and perspectives from forest research - Matyssek, Rainer (Developments in environmental science, 2013)
There are significant pressures from climate change and air pollution that forests currently face. This book aims to increase understanding of the state and potential of forest ecosystems to mitigate and adapt to climate change in a polluted environment. It reconciles process-oriented research, long-term monitoring and applied modeling through comprehensive forest ecosystem research. Furthermore, it introduces ""forest super sites for research? for integrating soil, plant and atmospheric sciences and monitoring. It also provides mechanistic and policy-oriented modeling with scientifically sound